Informalidade e desempenho econômico: Um análise dos impactors micro e macroeconômicos de políticas para a formalizaç\~ao - Gabriel Ulyssea (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper develops a framework for performing ex ante evaluations of the micro (at the firm level) and macro impacts of formalization policies. I estimate the model and use it analyze the two main policy approaches towards informality: increasing the costs of informality (the stick), and reducing the costs of formality (the carrot). The results show that there exist important tradeoffs between their micro and macro effects: while stick policies have uniformly worse effects on firms, their effects on aggregate outcomes are better than carrot policies. In net terms, however, stick policies have better welfare effects. Under either approach, informality reductions are not necessarily associated to welfare gains.
Keywords: O11; O12; O17; 330; informality; ex ante evaluations